Overset grid generation with inverse scattering technique for object and crack detection - Deanne Anak Edwin; Shafrida Sahrani; Kismet Anak Hong Ping (Universitas Ahmad Dahlan, 2020)
This paper presents the forward backward time stepping (FBTS) technique with finite difference time domain (FDTD) method and overset grid generation (OGG) method was applied for the reconstruction of object and crack detection. Object and crack detection is widely used in structural health monitoring (SHM) application especially in civil structure to detect the buried object and also cracks. The proposed numerical approach has been validated by investigating different kind of ratio of grid size between the main mesh and sub-mesh. Then, the proposed numerical approach is implemented in the analysis of the detection of objects such as concrete blocks and cracks underground. Here, the numerical errors between the actual result and simulated result had been calculated by using relative error. It is shown that the proposed approach has 5.22% error and nearer to the actual value.